FAKTOR DOMINAN PERILAKU KONTROL TEKANAN DARAH PADA PENDERITA HIPERTENSI - Hanafi Hanafi; Dina Palayukan Singkali; Agus Putra Murdani; Maritje F Papilaja (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Hypertension remains a major global health issue and a top priority. According to data from the Simalinyang Community Health Center (UPT Puskesmas Simalinyang), the incidence of hypertension is one of the health problems that has been increasing every year. The purpose of this study was to identify the dominant factors influencing blood pressure control behavior among patients with hypertension. A cross-sectional study design was used in this research. The study was conducted at the Simalinyang Community Health Center (UPT Puskesmas Simalinyang) in October 2025. The study population consisted of patients with hypertension who had visited the Simalinyang Community Health Center. The sample comprised 87 respondents. Simple random sampling was used to select the sample. A questionnaire was used as the research instrument. Data analysis was performed using univariate, bivariate and multivariate methods. The results showed that self-efficacy is a dominant variable influencing blood pressure control behavior in hypertensive patients, with a p-value of 0.005 and an odds ratio (OR) of 4.329. It is recommended that hypertensive patients adhere more strictly to a balanced diet to meet their nutritional needs and follow the diet recommended by healthcare professionals to control blood pressure and prevent the onset of other complications.Keywords: Self-Efficacy, Hypertension, Blood Pressure Control..